A review of Chiromantes obtusifrons (Dana, 1851) (Decapoda: Brachyura: Sesarmidae), with descriptions of four new sibling-species from Christmas Island (Indian Ocean), Guam and Taiwan - Davie, Peter J.f.; Ng, Peter K.l. (Zootaxa, 2013)
The identity of Chiromantes obtusifrons (Dana, 1851), previously considered widespread in the tropical West Pacific re-gion to the eastern Indian Ocean, is revised and found to be a species-complex. Chiromantes obtusifrons is now considered endemic to the Hawaiian Is., and four new species are described from Guam, Taiwan and Christmas Island. Two species live sympatrically in Taiwan. Species separation is based on carapace and frontal shape and granulation, leg proportions, abdominal somite proportions, and distinctive live colouration.